The Debate in Bioethics - Sgreccia, Elio (Medicina e Morale, 1989)
Representing the "Ethics and Medicine" Group of the Lanza Foundation of Padua, whose research I coordinate, I had the opportunity to participate on March 13 in the first debate of the Seminar "General Problems of Bioethics," organized at the Milan headquarters of "Pòliteia," a secular-inspired "center for research and training in politics and ethics" that explicitly refers to the liberal-democratic tradition.